Performance analysis of scheduling and dropping policies in vehicular delay-tolerant networks - Soares, V.N.G.J. (2011)
Vehicular Delay-Tolerant Networking (VDTN) was proposed as a new variant of a delay/disruptive-tolerant network, designed for vehicular networks. These networks are subject to several limitations including short contact durations, connectivity disruptions, network partitions, intermittent connectivity, and long delays. To address these connectivity issues, an asynchronous, store-carry-and-forward paradigm is combined with opportunistic bundle replication, to achieve multi-hop data delivery. Since VDTN networks are resource-constrained, for example in terms of communication bandwidth and storage capacity, a key challenge is to provide scheduling and dropping policies that can improve the overall performance of the network. This paper investigates the efficiency and tradeoffs of several scheduling and dropping policies enforced in a Spray and Wait routing scheme. It has been observed that these policies should give preferential treatment to less replicated bundles for a better network performance in terms of delivery ratio and average delivery delay.